Menggapai Keunggulan Promosi di Era Digital: Kolaborasi Canva untuk Peningkatan Ekonomi Lokal - M Riski Qisthiano; Doni Pramana (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
This research analyzes the potential for collaboration with graphic design platform Canva to generate promotional advantages for local businesses in the digital era and their impact on local economic growth. Amidst dynamic changes in consumer behavior and marketing trends, promotion is the key to local business success. Canva offers a solution for creating visually appealing content with minimal design skills, making it relevant for users of all backgrounds. This research deepens the understanding of the effectiveness of promotional campaigns, increased brand visibility, and higher audience engagement through the use of Canva. However, this research also considers the limitations in using this platform, including the risk of uniform content that is less unique. The practical implications of this research are to guide local businesses in designing more effective promotions through the Canva platform, increasing interaction with consumers, and contributing to local economic growth. With a focus on the Canva collaboration, this research provides insight into how this graphic design platform can become a strategic tool in achieving business promotion and development goals in the digital age.